Pendampingan Guru dalam Pencegahan Sindrom Metabolik di SMA N 1 Bergas, Kabupaten Semarang - Afiatna, Puji; Sugeng Maryanto; Umi Setyoningrum; Untari; Anisa Puspitasari (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Metabolic syndrome is a condition that can lead to the development of cardiovascular disease (CVD), coronary heart disease (CHD), and type 2 diabetes mellitus (T2DM). These diseases are frequently referred to as "noncommunicable diseases," and they account for the highest global mortality rates. The occupation of school teachers has been identified as a profession with a high risk of obesity. This is due to the fact that teachers engage in relatively sedentary daily activities, exhibit excessive eating patterns, frequently engage in snacking, and consume foods that are high in calories and carbohydrates. This condition places school teachers at high risk of developing metabolic syndrome and may adversely impact their performance. It is imperative to enhance our understanding and competencies regarding metabolic syndrome and its prevention. A series of educational initiatives have been implemented to promote the prevention of metabolic syndrome among teaching professionals. These initiatives employ a multifaceted approach, incorporating lecture-style presentations, interactive discussions, and hands-on demonstrations. The content of these sessions encompasses an in-depth examination of metabolic syndrome, its underlying causes, the ramifications it can have on individuals, and effective strategies for its prevention. Prior to the commencement of the activity, a series of anthropometric measurements and health assessments were conducted. Additionally, the presentation encompassed material on the role of functional foods in the prevention of metabolic syndrome, along with the processing of healthy foods. Demonstrations of food portioning according to nutritional needs and metabolic syndrome prevention exercises were carried out. The results obtained after the material was administered revealed a 26.55-point increase in the average score of teacher knowledge. A substantial majority of teachers exhibit a commendable degree of pedagogical expertise, with a notable 93.1% demonstrating a high level of proficiency. Teachers' curiosity about the prevention of metabolic syndrome has been shown to encourage active participation in activities. The subject displays a high level of motivation.   ABSTRAK Sindrom metabolik merupakan kondisi yang dapat berkembang menjadi penyakit  gagal jantung (CVD), jantung coroner (CHD) dan diabetes melitus tipe 2 (T2DM). Penyakit tersebut yang sering disebut ”noncommunicable diseases” dan penyebab utama kematian di dunia. Guru sekolah merupakan kelompok dengan risiko obesitas tinggi karena memiliki aktivitas harian tergolong ringan, pola makan yang berlebih, sering ngemil, makan makanan tinggi kalori dan karbohidrat. Kondisi ini menyebabkan guru sekolah berisiko tinggi mengalami sindrom metabolik dan akan berdampak pada performa guru. Diperlukan peningkatan pengetahuan dan keterampilan menganai sindrom metabolik dan pencegahannya. Kegiatan pendampingan pencegahan sindrom metabolik pada guru dilakukan dengan metode ceramah, diskusi dan demonstrasi mengenai sindrom metabolik, faktor penyebab, dampak dan pencegahannya. Kegiatan didahului dengan pengukuran antropometri dan pemeriksaan kesehatan. Selanjutnya disampaikan materi mengenai pangan fungsional untuk pencegahan sindrom metabolik dan pengolahan makanan yang sehat. Dilakukan demonstrasi pemorsian makanan sesuai kebutuhan gizi dan senam pencegahan sindrom metabolik. Hasil yang didapat setelah diberikan materi adalah meningkatnya rerata skor pengetahuan guru  sebesar 26,55 poin. Hampir seluruh guru memiliki tingkat pengetahuan guru menjadi baik (93,1%). Keingintahuan guru yang mengenai pencegahan sindrom metabolik menjadi penyemangat guru untuk aktif mengikuti kegiatan. Motivasi yang tinggi untuk memiliki pola makan dan pola hidup yang lebih sehat merupakan dasar perubahan perilaku menjadi perilaku yang lebih sehat.